Glucose-Specific Enzyme IIA of the Phosphoenolpyruvate:Carbohydrate Phosphotransferase System Modulates Chitin Signaling Pathways in Vibrio cholerae - Yamamoto, Shouji; Ohnishi, Makoto (Journal of bacteriology, 2017)
In Vibrio cholerae , the genes required for chitin utilization and natural competence are governed by the chitin-responsive two-component system (TCS) sensor kinase ChiS. In the classical TCS paradigm, a sensor kinase specifically phosphorylates a cognate response regulator to activate gene expression. However, our previous genetic study suggested that ChiS stimulates the non-TCS transcriptional regulator TfoS by using mechanisms distinct from classical phosphorylation reactions (S. Yamamoto, J. Mitobe, T. Ishikawa, S. N. Wai, M. Ohnishi, H. Watanabe, and H. Izumiya, Mol Microbiol 91:326–347, 2014, https://doi.org/10.1111/mmi.12462 ). TfoS specifically activates the transcription of tfoR , encoding a small regulatory RNA essential for competence gene expression. Whether ChiS and TfoS interact directly remains unknown. To determine if other factors mediate the communication between ChiS and TfoS, we isolated transposon mutants that turned off tfoR :: lacZ expression but possessed intact chiS and tfoS genes. We demonstrated an unexpected association of chitin-induced signaling pathways with the glucose-specific enzyme IIA (EIIA glc ) of the phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) for carbohydrate uptake and catabolite control of gene expression. Genetic and physiological analyses revealed that dephosphorylated EIIA glc inactivated natural competence and tfoR transcription. Chitin-induced expression of the chb operon, which is required for chitin transport and catabolism, was also repressed by dephosphorylated EIIA glc . Furthermore, the regulation of tfoR and chb expression by EIIA glc was dependent on ChiS and intracellular levels of ChiS were not affected by disruption of the gene encoding EIIA glc . These results define a previously unknown connection between the PTS and chitin signaling pathways in V. cholerae and suggest a strategy whereby this bacterium can physiologically adapt to the existing nutrient status. IMPORTANCE The EIIA glc protein of the PTS coordinates a wide variety of physiological functions with carbon availability. In this report, we describe an unexpected association of chitin-activated signaling pathways in V. cholerae with EIIA glc . The signaling pathways are governed by the chitin-responsive TCS sensor kinase ChiS and lead to the induction of chitin utilization and natural competence. We show that dephosphorylated EIIA glc inhibits both signaling pathways in a ChiS-dependent manner. This inhibition is different from classical catabolite repression that is caused by lowered levels of cyclic AMP. This work represents a newly identified connection between the PTS and chitin signaling pathways in V. cholerae and suggests a strategy whereby this bacterium can physiologically adapt to the existing nutrient status.